Vitamins C and D (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The global coronavirus pandemic has highlighted the paramount importance of immune health and the nutrient status of peoples worldwide. Vitamins C and D have important roles in both the innate and adaptive immune systems and are known to support healthy immune function. Both vitamins C and D have gene regulatory roles with the ability to up- and down-regulate thousands of genes, thus playing pleotropic roles in human health and disease. People from low- and middle-income countries tend to have inadequate micronutrient intakes and status, as do specific subgroups from high-income countries. This can affect their resistance to both communicable and non-communicable diseases and the severity of these diseases. In this Special Issue, we have compiled review articles and research papers (both observational and interventional studies) that explore the role of vitamins C and D in numerous aspects of global and population health.